Potential vectors of Plum pox virus in the Eastern Mediterranean Region of Turkey - Kaya, Kamuran; Gazel, Mona; Serce, Cigdem Uluba; Elci, Eminur; Cengiz, Feza Can; Cambra, Mariano; Caglayan, Kadriye (2017)
Although Plum pox virus (PPV) was first detected in Turkey 44 years ago, the virus is present in a rather limited number of trees. Our recent studies on PPV incidence showed that PPV was introduced rapidly in PPV-free regions and that there are no data available about the role of aphid species and Prunus rootstocks on these new infections. In this study the epidemiological aspect of PPV was studied in Antakya-Hatay, located in the Eastern Mediterranean region of Turkey where PPV was first detected in 2011. The susceptibility of different Prunus rootstocks to PPV was evaluated in an established experimental plot next to a PPV-infected nectarine orchard. Aphid populations were monitored in 2011 and 2012 from the last week of April to the middle of June by the sticky-plant method in both the experimental plot (EP) and the surrounding infected nectarine orchard (SNO). Regularly collected plant samples and aphids were individually tested by DASI-ELISA and squash real-time RT-PCR, respectively. The highest aphid population densities were observed at the end of May in both years. The most abundant aphid species were Aphis gossypii and A. spiraecola both in EP and SNO in both years. The percentage of PPV-viruliferous Myzus persicae, A. fabae, A. gosypii, A. spiraecola, Hyalopterus pruni, Macrosiphon euphorbiae and A. craccivora as estimated by squash real-time RT-PCR were 39.47%, 25.00%, 24.56%, 22.60%, 22.22%, 20.00% and 8.00%, respectively. The percentages of viruliferous aphids collected from SNO were 12.5% in A. spiraecola, 12.42% in A. gossypii and 11.11% in H. pruni. At the end of 2012, three Myrobolan 29C and two Adesoto 101 rootstocks were found infected by PPV. Molecular characterization studies showed that PPV-M was the strain present in both the originally infected nectarine plot and the Myrobolan 29C rootstocks.